Fish Consumption Diversity Among the Adult Population of Rural Bangladesh (Bioresearch Communications, 2026)
The fisheries sector occupies a pivotal position in Bangladesh’s economy, livelihoods, culture, and nutrition. The current study aimed to explore the diversity in fish consumption and sociodemographic factors associated to fish intake among the Bangladeshi adult rural population. Data from the Bangladesh Integrated Household Survey (BIHS 2018-2019) was used for the current study. Data processing and statistical analysis was done using IBM SPSS version 31.0 and R version 4.5.1. Geometric mean (95% CI) was used to express average fish intake of the respondents and partial proportional odds model was used to explore the factors associated to fish intake among the adult population (age:19-59 years) of rural Bangladesh. Adults (19–59 years) have the highest average fish intake (males 46.47 g/day; females 38.63 g/day), exceeding adolescents (males: 41.04 g/day; females: 35.51 g/day), older adults 60+ (males: 41.75 g/day; females: 34.61 g/day), and children